Germline , variants in a patient with breast and ovarian cancer at risk for familial cancer syndrome: Is there a role for risk-reducing salpingo-oophorectomy? - Semiramis L. Carbajal-Mamani; Merry J. Markham; Joaquín Santolaya-Forgas; Jacqueline C. Castagno; Joel Cardenas-Goicoechea (Korean Society of Obstetrics and Gynecology, 2020)
A 50-year-old non-Hispanic white Caucasian female was diagnosed with breast cancer and was subsequently found to possess the tumorigenic ataxia telangiectasia mutated (ATM) and PALB2 variants but not the BRCA1 and BRCA2 variants. She visited the gynecologic oncology office for routine counseling about risk-reducing salpingo-oophorectomy (RRSO). Although the patient was asymptomatic, an adnexal mass was discovered in the physical examination performed by palpation. Upon using pre-operative imaging techniques, an 8 cm complex adnexal mass was identified. Her CA-125 level was elevated. She underwent complete cytoreductive surgery. Pathological analysis showed a stage IC clear cell carcinoma of the left ovary; subsequently, she received 6 cycles of adjuvant chemotherapy with a combination of carboplatin and paclitaxel. The patient exhibited no signs ovarian cancer in a follow-up appointment after 32 months of treatment. However, bilateral RRSO is not recommended for patients positive for ATM and PALB2. Breast cancer patients with PALB2 and ATM mutations should extensively discuss the risks and benefits of RRSO in light of current data.